Pancreatic Pseudocyst with Fistula to the Common Bile Duct Resolved by Combined Biliary and Pancreatic Stenting – A Case Report and Literature Review - Jaber A Al Ali; Henry Chung; Peter L Munk; Michael F Byrne (Canadian Journal of Gastroenterology)
Pancreatic pseudocysts develop in 10% to 20% of patients with chronic pancreatitis, and can cause a variety of complications such as infection, bleeding or development of fistulae. However, fistulous communication with the common bile duct is very rare. The present report describes an unusual case of a patient with a large, symptomatic pancreatic pseudocyst with a fistula to the common bile duct that was treated successfully by combined biliary and pancreatic stenting.